Connecting the past and the future: Academic geographical (im)mobility of Chinese women academics throughout doctoral education - Bao, Li (Frontiers in Psychology, 2022)
Introduction Academic geographical mobility is considered to be critical to academic excellence, but it is a gendered terrain. This study seeks to examine the career progression of Chinese women academics, as shaped by gender norms, regarding academic geographical (im)mobility throughout their doctoral education, in retrospect. Methods To address this issue, driven by the Butlerian theoretical concept of “a stylized repetition of acts,” the present study analyzed the qualitative data from semi-structured interviews with seven Chinese women academics to investigate their academic geographical mobility decisions throughout their doctoral education based on contested discourses of traditional Chinese culture and the advantages of academic geographical mobility for their career advancement. Results and discussion This study determined that, shaped by gender norms, stylized geographical academic (im)mobility for these Chinese female doctoral students operate in the condition of gender- norms maintenance to make them recognizable and understandable in social and institutional culture. However, it may have a negative impact on their future academic career progression.